2011
DOI: 10.1111/j.1600-0846.2011.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

The objective evaluation of the severity of psoriatic scales with desquamation collecting tapes and image analysis

Abstract: The results of this study showed that the severity of psoriatic scales could be measured objectively using the Corneofix(®).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
10
0
2
Order By: Relevance
“…To improve the statistical power, both PSI scores and histopathological grading should be upgraded to more precise, detailed, and continuous numerical parameters. Some studies have used objective bioengineering measurements to overcome the subjectivity of the PSI score 6 , 7 . Measurements of color, elasticity, and scale could be good substitutes for the PSI score without inter- or intra-rater variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the statistical power, both PSI scores and histopathological grading should be upgraded to more precise, detailed, and continuous numerical parameters. Some studies have used objective bioengineering measurements to overcome the subjectivity of the PSI score 6 , 7 . Measurements of color, elasticity, and scale could be good substitutes for the PSI score without inter- or intra-rater variability.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the correlation between quantitative histopathological grading systems and the clinical types of psoriasis, to determine whether histopathological grading could be used as a new tool for evaluating psoriasis severity. In addition, we intended to correlate the histopathological findings with the psoriasis severity index (PSI) score 6 , 7 , to elucidate whether the conventional clinical severity scoring tools could express histopathological severity so that evidence-based psoriasis severity assessment tools can be developed.…”
Section: Introductionmentioning
confidence: 99%
“…In future research, the erythema intensity determined using the proposed system will be confirmed by comparison with indices, such as the erythema index (EI), melanin index (MI) and TiVi value, determined using other devices . In addition, to validate the proposed system's applicability, further studies involving lighter or darker skin types are warranted.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, their work did not primarily focus on severity itself. Kim et al 11 used desquamation collecting tapes along with image analysis as a method of objectively measuring the degree of psoriatic scaling. Xhauflaire-Uhoda et al 12 and Pierard-Franchimont et al 13 tried to represent the severity of psoriasis in terms of capacitance.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, their work did not primarily focus on severity itself. Kim et al . used desquamation collecting tapes along with image analysis as a method of objectively measuring the degree of psoriatic scaling.…”
Section: Discussionmentioning
confidence: 99%